Implementasi Metode SMARTER dan TOPSIS Pada Sistem Pendukung Keputusan Pemilihan Bibit Cabai Merah Yang Unggul - Putri Sri Rezeki; Muhammad Dedi Irawan; Fathiya Hasyifah Sibarani (LPPM Universitas Putera Batam, 2026)
The productivity of red chili cultivation highly depends on the quality of seeds used by farmers. However, identifying superior red chili seeds is often difficult, leading to low yields and even crop failure. This study aims to design a Decision Support System (DSS) for selecting superior red chili seeds using the SMARTER (Simple Multi Attribute Rating Technique Exploiting Rank) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) methods. The SMARTER method is applied to determine the weight of each criterion based on the Rank Order Centroid (ROC), while the TOPSIS method is used to rank alternative seed varieties. Seven criteria were considered: price, disease resistance, harvest time, fruit length, fruit weight, number of branches, and yield potential. The system was developed using a waterfall model and implemented in a web-based application with PHP and MySQL. The results showed that the best-ranked alternative was the Tangguh F1 variety with a preference value of 0.7429, followed by Kastilo and TM999. The developed DSS provides structured, efficient, and transparent recommendations, thus helping farmers and agricultural agencies in decision-making for selecting superior red chili seeds.